Membrane translocation of TRPC6 channels and endothelial migration are regulated by calmodulin and PI3 kinase activation - Chaudhuri, Pinaki (2016)
Lipid oxidation products, including lysophosphatidylcholine (lysoPC), activate canonical transient receptor potential 6 (TRPC6) channels leading to inhibition of endothelial cell (EC) migration in vitro and delayed EC healing of arterial injuries in vivo. The precise mechanism through which lysoPC activates TRPC6 channels is not known, but calmodulin (CaM) contributes to the regulation of TRPC channels. Using site-directed mutagenesis, cDNAs were generated in which Tyr99 or Tyr138 of CaM was replaced with Phe, generating mutant CaM, Phe99-CaM, or Phe138-CaM, respectively. In ECs transiently transfected with pcDNA3.1-myc-His-Phe99-CaM, but not in ECs transfected with pcDNA3.1-myc-His-Phe138-CaM, the lysoPC-induced TRPC6-CaM dissociation and TRPC6 externalization was disrupted. Also, the lysoPC-induced increase in intracellular calcium concentration was inhibited in ECs transiently transfected with pcDNA3.1-myc-His-Phe99-CaM. Blocking phosphorylation of CaM at Tyr99 also reduced CaM association with the p85 subunit and subsequent activation of phosphatidylinositol 3-kinase (PI3K). This prevented the increase in phosphatidylinositol (3,4,5)-Trisphosphate (PIP3) and the translocation of TRPC6 to the cell membrane and reduced the inhibition of ECmigration by lysoPC. These findings suggest that lysoPC induces CaM phosphorylation at Tyr99 by a Src family kinase and that phosphorylated CaM activates PI3K to produce PIP3, which promotes TRPC6 translocation to the cell membrane.